Research on Dynamic Maintenance System of Electrical Automation Secondary Equipment in Smart Substation - Yanan Wang , Juanjuan Wang (Forest Chemicals Review)
At present, the development of power grids is deeply integrated with information technologies such as "Big Cloud IoT Chain". The power grid takes the secondary equipment online monitoring and intelligent diagnosis device as the edge agent, and applies it to analyze and process the secondary equipment operation, alarm, action and other information on the spot. The system realizes secondary equipment operation analysis and abnormal dynamic diagnosis. This paper proposes the overall system architecture and dynamic diagnosis scheme of the secondary equipment dynamic diagnosis technology based on deep learning. Key contents such as plug and play, diagnostic model, automatic generation of IED database, online evaluation and dynamic reconstruction are discussed. The research shows that the method can analyze the defects and find the weak links of the secondary equipment, which provides support for the formulation of defect inspection methods and the formulation of maintenance strategies.